2003
DOI: 10.1080/00224490309552162
|View full text |Cite
|
Sign up to set email alerts
|

Gender matters: Constructing a model of adolescent sexual health

Abstract: This article illustrates the construction of a new model of adolescent sexual health, one that addresses the complex relationships between gender and adolescent sexuality. A review of sexual health models highlights the absence of gender; in contrast, research illuminates the significance of gender. This article describes the process of building a model of sexual health explicitly for girls, guided by feminist research on adolescent girls' sexuality and a "web of theories". It also describes the unanticipated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(211 citation statements)
references
References 34 publications
11
193
1
6
Order By: Relevance
“…Some participants believe that lack of strong religious beliefs can be a threat to sexual health which is in accordance with the study by Michael et al 25 , He reported lack of religious beliefs as a factor for deviation from sexual behavior. The increased incidence of high-risk sexual behaviors is also discussed by most participants as the threatening factor of sexual health which can increase the incidence of sexually transmitted diseases and its negative consequences 26 . Addiction is also introduced as another factor which threatens sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants believe that lack of strong religious beliefs can be a threat to sexual health which is in accordance with the study by Michael et al 25 , He reported lack of religious beliefs as a factor for deviation from sexual behavior. The increased incidence of high-risk sexual behaviors is also discussed by most participants as the threatening factor of sexual health which can increase the incidence of sexually transmitted diseases and its negative consequences 26 . Addiction is also introduced as another factor which threatens sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies would benefit from focused attention according to Eyre's (1997) recommendations for eliciting adolescents' own interpretations of vernacular terms and their cultural connotations. Although population-level data on health practices and infection rates serve an important function, research designed to understand the sociocultural context for sexual risk-taking is needed to develop appropriate prevention strategies (Beatty, Wheeler, & Gaiter, 2004;Kreuter & Haughton, 2006;Tolman, Striepe, & Harmon, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Kimmel concludes that the variation within the attributes associated with masculinity and femininity are far greater than the differences between the two (Kimmel, 2000). Perhaps most salient about this measurement paradigm is that it forces a singular, atheoretical resolution to the number of theoretical descriptions of gender that are held by adolescence researchers (Tolman, Striepe, & Harmon, 2003). These include evolutionary theory (Buss, 1996;Thornhill & Palmer, 2000), social role theory (Pleck, 1987;Eagly & Wood, 1999;Spence, 1993), and social construction theory (Butler, 1993;Gergen, 1985).…”
Section: Caveatsmentioning
confidence: 99%